2018
DOI: 10.3390/polym10101124
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of the 3-pentadecyl-phenol In Situ Modified Foamable Phenolic Resin

Abstract: In this present study, 3-pentadecyl-phenol was selected as a modifier to prepare a foamable phenolic resin with excellent performance, which was successfully prepared by in situ modification. Fourier transform infrared spectroscopy (FT-IR) and nuclear magnetic resonance (1H NMR, 13C NMR) were used to test and characterize the molecular structure of the modified resin. The results showed that 3-pentadecyl-phenol successfully modified the molecular structure of phenolic resin with a reduction in the resin gel ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Polypropylene (PP) foam is widely used in daily necessities, military industries, transportation, and aerospace, such as in the production of various seat cushions, thermal insulation materials, shockproof materials, packaging materials, and building materials [16,17,18]. Phenolic foam is mainly used in the fields of architecture, automobiles, electrical and electronic applications, the iron and steel industry, and aerospace [19,20,21,22]. It can meet the requirements of heat insulation and combustion-resistant building materials for large-scale sports and entertainment venues, high-rise buildings, and high-speed vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Polypropylene (PP) foam is widely used in daily necessities, military industries, transportation, and aerospace, such as in the production of various seat cushions, thermal insulation materials, shockproof materials, packaging materials, and building materials [16,17,18]. Phenolic foam is mainly used in the fields of architecture, automobiles, electrical and electronic applications, the iron and steel industry, and aerospace [19,20,21,22]. It can meet the requirements of heat insulation and combustion-resistant building materials for large-scale sports and entertainment venues, high-rise buildings, and high-speed vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…There are absorption peaks at 756.10 cm −1 in the ortho-substitution bending vibration region of the benzene ring, and 829.12 cm −1 in the para-substitution bending vibration region of the benzene ring. The IR bands of the C–O group of phenol and C–O group of hydroxymethyl appeared at 1153.18 cm −1 and 1108.32 cm −1 [2]. Compared with the basic phenolic resin, the IR spectra of polyether phenolic resin showed that the stretching vibration peaks of the polyether methylene are located at 2937.54 cm −1 and 2860.77 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2, δ = 6.5–7.4 ppm at position h is the proton peak of hydrogen in the benzene ring, δ = 4.8–5.1 ppm at position f is the proton peak of hydrogen in phenol, δ = 4.2–4.7 ppm at position e is the hydrogen proton peak of the methyl group in the hydroxymethyl group, δ = 3.6–3.8 ppm at position d is the proton peak of the hydrogen in the linking benzene ring –CH 2 –, and δ = 1.9–2.1 ppm at position c is the hydrogen proton peak of hydroxymethyl –OH [2]. Compared with the basic phenolic resin, the 1 H NMR spectra of polyether phenolic resin showed that the δ = 1.0–1.2 ppm at position a is the hydrogen proton peak of hydrogen in the polyether skeleton, while δ = 1.7–1.8 ppm at position b is the hydrogen proton peak of hydrogen in the terminal methyl group of acetoacetic ester, while δ = 5.8–5.9 ppm at position g is the hydrogen proton peak of hydrogen in the methylene group of acetoacetic ester.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations